The effect of expansive open-door laminoplasty on spinal canal diameter: an experimental study on rabbits - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2013)
Objective: The aim of this experimental study was to evaluate the effect of expansive open-door laminoplasty with simple suture fixation on spinal canal diameter in a rabbit model. Methods: Twenty white New Zealand rabbits were operated on with C4-C7 Hirabayashi open-door laminoplasty. The spinal canal diameter was evaluated radiologically on preoperative day 1 and postoperative days 1 and 42. Results: The mean spinal canal diameter was 6.42 mm preoperatively, 8.04 mm on postoperative day 1 and 8.02 mm at day 42. There was a significant difference between the mean preoperative and postoperative day 1 spinal canal diameter (p<0.001). There was no significant difference between the mean spinal canal diameter at postoperative day 1 and 42 (p>0.05). Conclusion: Our results suggest that the open-door laminoplasty with simple suture fixation is an effective method to expand the spinal canal diameter. No recurrent narrowing is expected in short term.
Keywords: Expansion; laminoplasty; myelopathy; reclosure; spinal canal; TECHNICAL IMPROVEMENTS; CERVICAL LAMINOPLASTY; MYELOPATHY; OSSIFICATION; LAMINECTOMY